2018
DOI: 10.1155/2018/3842753
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Regulates the Proliferation of Human Glioma Cells through miR-214 and E2F2

Abstract: Peroxisome proliferator-activated receptor α (PPARα) is a member of the nuclear hormone receptor superfamily and functions as a transcription factor. Previous work showed that PPARα plays multiple roles in lipid metabolism in tissues such as cardiac and skeletal muscle, liver, and adipose tissue. Recent studies have discovered additional roles for PPARα in cell proliferation and metabolism, as well as tumor progression. PPARα is aberrantly expressed in various cancers, and activated PPARα inhibits the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Previous study reported that miR-199a-5p significantly regulated cell proliferation, migration, and invasion. 18,22,23 In glioma, Zhang et al reported that miR-199a inhibits tumor growth and attenuates chemoresistance by targeting K-RAS via ATK and ERK signaling. 24 Our previous study also found that miR199a-5p suppresses glioma cell proliferation, migration, and invasion by inhibiting MAGT1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that miR-199a-5p significantly regulated cell proliferation, migration, and invasion. 18,22,23 In glioma, Zhang et al reported that miR-199a inhibits tumor growth and attenuates chemoresistance by targeting K-RAS via ATK and ERK signaling. 24 Our previous study also found that miR199a-5p suppresses glioma cell proliferation, migration, and invasion by inhibiting MAGT1.…”
Section: Discussionmentioning
confidence: 99%
“…GSE103229 (https://www.ncbi.nlm.nih.gov/geo/query/acc .cgi?acc=GSE103229) contains five nontumor brain tissues and five glioma tissues. The GSE4290 and CGGA database information refers to our previous description [33,34]. TCGA (https://www.cancer.gov/about-nci/organization/ccg/research/ structural-genomics/tcga) contains 555 glioma specimens, including 210 in the World Health Organization (WHO) II, 233 in the WHO III, and 112 in the WHO IV.…”
Section: Methodsmentioning
confidence: 99%
“…The CGGA contains 301 glioma samples (including 84 astrocytoma, 89 oligodendroglioma and 128 glioblastoma samples). The grouping of low-grade glioma (LGG), AG and GBM was performed as previously described (14). The GSE16011 dataset () contains 276 glioma samples (including samples from 8 patients with epilepsy and 24 astrocytoma, 85 oligodendroglioma and 159 glioblastoma samples) and 8 control samples, totaling 284 specimens (15).…”
Section: Methodsmentioning
confidence: 99%